2016
DOI: 10.1093/infdis/jiw485
|View full text |Cite
|
Sign up to set email alerts
|

Identification ofChlamydia trachomatisAntigens Recognized by T Cells From Highly Exposed Women Who Limit or Resist Genital Tract Infection

Abstract: Investigations in naturally exposed women reveal protective responses and identify chlamydial vaccine candidate antigens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 35 publications
3
29
2
Order By: Relevance
“…We next investigated the association between chlamydia load and ascension. Cervical burden was significantly lower in 56 women with cervical infection only, compared to 39 women with endometrial infection ( P = 3.51E‐08, t test; Figure ), consistent with prior findings within the cohort . Finally, we performed a causal mediation analysis to test whether antibody impacted ascension (Figure ).…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…We next investigated the association between chlamydia load and ascension. Cervical burden was significantly lower in 56 women with cervical infection only, compared to 39 women with endometrial infection ( P = 3.51E‐08, t test; Figure ), consistent with prior findings within the cohort . Finally, we performed a causal mediation analysis to test whether antibody impacted ascension (Figure ).…”
Section: Resultssupporting
confidence: 80%
“…Cervical and endometrial swab samples were tested for C trachomatis, Neisseria gonorrhoeae, and Mycoplasma genitalium using nucleic acid amplification tests (NAAT; Aptima Combo 2; Gen‐Probe, and APTIMA MG; Gen‐Probe) as described previously . Cervical chlamydia burden was estimated via quantitative PCR using genomic DNA extracted from reserved cervical swab eluates as template . Women with positive cervical and endometrial Chlamydia NAATs were designated Endo+, while those with a positive cervical NAAT only were defined as Endo−.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some T3SS proteins are surface-exposed and can be targeted by neutralizing antibodies. The T cell response to T3SS antigens was recently shown to be associated with protection against C. trachomatis infection in highly exposed women [13], and T3SS components have recently attracted attention as vaccine candidates against other pathogenic bacteria [1417]. The C. trachomatis T3SS filament protein, CdsF, and its orthologs in other bacteria form the needles of injectisomes and are believed to facilitate the insertion of translocators into the host cell membrane [11, 12, 18].…”
Section: Introductionmentioning
confidence: 99%
“…A small study of adolescent women demonstrated that IFN-γ production by CD4 + T-cells trended towards a reduced risk for reinfection [8]. Another study showed an increased in the frequency of IFN-γ-producing CD4 + T-cells in women without incident CT infection compared to women with CT infection [9]. Further support for the protective role of IFN-γ comes from an immunoepidemiologic study of commercial sex workers that showed a reduced risk for incident Ct infection was associated with the Th1 cytokine IFN-γ and also the Th2 cytokine IL-13 [10].…”
Section: Introductionmentioning
confidence: 99%